Mesenchymal stromal cells in the treatment of pediatric hematopoietic cell transplantation-related complications (graft vs. host disease, hemorrhagic cystitis, graft failure and poor graft function): a single center experience - Pérez-Torres Lobato, Maria; Benitez-Carabante, Maria Isabel; Alonso, Laura; Torrents, Silvia; Castillo Flores, Nerea; Uria Oficialdegui, Maria Luz; Panesso, Melissa; Alonso-Martínez, Carla; Oliveras, Maria; Renedo-Miró, Berta; Vives, Joaquim; Diaz-de-Heredia, Cristina (Frontiers in Pediatrics, 2024)
Objectives To describe mesenchymal stromal cells (MSCs) in the treatment of hematopoietic stem cell transplantation (HSCT) complications and to assess its safety and efficacy. Methods Single-center retrospective study (2016–2023). Patients under 20 years who received MSCs for the treatment of HSCT-related complications were included. Results Thirty patients (53.7% boys), median age at transplant 11 years (range 2–19) were included. MSCs indications were: graft-vs.-host disease (GVHD) in 18 patients (60%), of them 13 had acute GVHD (43.3%) and 5 chronic GVHD (16.7%); Grade 3–4 hemorrhagic cystitis (HC) in 4 (13.3%); poor graft function (PGF) in 6 (20%), 5 of them receiving MSCs with a CD34 stem cell-boost coinfusion; graft failure (GF) in 2 (6.7%), to enhance engraftment after a subsequent HSCT. Infusion-related-adverse-events were not reported. Overall response (OR) was 83% (25/30); 44% of responders (11/25) showed complete response (CR). OR for GVHD, HC, PGF and GF was 83.3%, 100%, 66.7% and 100% respectively. Response rate was 40% (95% CI: 20–55) and 79% (95% CI: 57–89) at 15 and 30 days. With a median follow-up of 21 months (IQR11–52.5), overall survival (OS) was 86% (95% CI: 74–100) and 79% (95% CI: 65–95) at 6 and 12 months post-MSCs infusion. Conclusion In our study, the most frequent indication of MSCs was refractory aGVHD (43.3%). Response rates were high (OR 83%) and safety profile was good.